(untitled) (SCIÉNDO INGENIUM, 2022)
This applied research, with a non-experimental, transectional, descriptive-correlational design and a Deductive-Analytical-Synthetic method, had the purpose of analyzing the relationship between the teaching tutorial work and the formative process of the university students at the National University of San Martín; For which, two opinion questionnaires and two multiple-choice questionnaires, valid and reliable, were applied to a stratified sample of 223 students from the 20 study programs of the X cycle; It the student perception it was found a regular teaching tutorial work; the most frequent level of teaching tutorial work was high, 47.1%, as well as in the personal dimension, 46.2% and professional 45.8%, while it was medium in the academic dimension, 47.5 %; the most frequent level of formative process was regular, 48.9%, as well as in the dimensions of entrance, 48.4%, permanence, 46.2% and completion, 44.8%; there is a highly significant relationship between teaching tutorial work and the formative process of the students (p-value <0.01), as well as between academic, personal and professional dimensions with the formative process (p-value <0.01); likewise, the proposal of the Quality Tutorial Management Model is based on the philosophical theory of humanism, with a socioformative, sociocultural, approach and the philosophy of administration proposed by Deming’s.